Eksegesis Kitab Daniel - Bartholomeus Diaz Nainggolan (Fakultas Filsafat Universitas Advent Indonesia, 2013)
Why is the book of Daniel is an attractive study? One thing is because it described the loyalty of Hebrew young people to God, although they are in captivity. Their experiences provides insights into how to behave when facing difficult circumstances and are tempted to sacrifice faith. The Book of Daniel contains dreams, imaginations, and an interesting interpretation that underscores the way and purpose of history, the rise and falls of great kingdoms, God’s intervention in human events, how the people of God will be persecuted, and how everything works for good. If you want to know the fate of the human race, to know the current era, then learn the Daniel’s prophecy. Ellen G. White admonish to read the book of Daniel because the light that God gave to Daniel's regarding the end of time is special and this is very important.